Development of Management Information System Based on MVC Architecture to Improve Business Process Efficiency - Miftahul Jannah; Dahlan; Chairul Akbar (Journix: Journal of Informatics and Computing, 2025)
With the increasing need for flexible, scalable, and maintainable information systems, the Model-View-Controller (MVC) architecture has become a popular approach in software development. This research aims to design and implement an MVC-based management information system to improve data management and business process efficiency. The study adopts the Agile software development method with the Scrum framework, enabling iterative progress and rapid adaptation to user needs. The implementation employs the Laravel framework to ensure modular separation between business logic, user interface, and control flow. The evaluation is carried out using black-box testing and performance testing with Apache JMeter. The results show that the MVC-based system reduces processing time by 30% compared to a monolithic system and enhances system scalability and maintainability. This study concludes that MVC architecture provides significant improvements in system efficiency, modularity, and sustainability. Future work may focus on integrating microservices and cloud computing to further enhance scalability and performance.